Reproductive health programs in women with physical disabilities: A scoping review protocol - Maryam Abedi; Mehran Soleymani; Seyedeh Solmaz Talebi; Zahra Motaghi (PLoS ONE, 2025)
Introduction Approximately 15% of people with disabilities are women of reproductive age. Women with physical disabilities are neglected in reproductive and sexual health. Complex health conditions, mobility limitations, negative disability stereotypes, and misconceptions about their needs directly and indirectly affect their sexual and reproductive health. Access to appropriate reproductive health care is crucial for empowering these women to manage their reproductive and sexual health challenges effectively. This scoping review aims to identify, explore, and map the existing evidence on reproductive health programs and interventions in women with physical disabilities. Materials and methods This scoping review will be based on Arksey and O’Malley’s methodological framework and the subsequent recommendations of Levac et al. We will search for studies published from January 2006–2024 in English and Persian without restriction by study design in databases such as Web of Science, PubMed, ProQuest, Springer, Google Scholar, ScienceDirect, Cochrane Library, Agency for Healthcare Research and Quality, and websites like the World Health Organization, UNICEF and government sites for policies and reports about reproductive health programs for women with physical disabilities. Two or more reviewers will independently conduct all stages of the study. Data synthesis will utilize a qualitative analysis approach, and this review will be reported using the PRISMA-ScR checklist. Conclusion This scoping review synthesizes evidence on reproductive health interventions for women with physical disabilities, including educational and awareness programs, healthcare access initiatives, support groups, and policy interventions. We will explore these interventions across various dimensions of reproductive health. The results of this review will offer a comprehensive overview of available resources and identify critical gaps in reproductive health for this population. To our understanding, this study may be the first scoping review in this field, which could provide valuable guidance to key stakeholders.